Effectiveness of nutritional intervention on immunity among people living with HIV/AIDS: a systematic review - John, Stephen; Natekar, Dileep S. (International Journal Of Community Medicine And Public Health, 2024)
A huge progress is made in the treatment modality of human immunodeficiency virus and acquired immunodeficiency syndrome (HIV/AIDS). To develop cure or enhance immunity of people living with HIV/AIDS (PLHIV), major researches are being conducted across the globe. Nutritional interventions are experimented widely over a period of time in improving immunity among PLHIV but concrete evidence in this regard is doubted still. This study aimed to assess the effectiveness of selected nutritional interventions (zinc) on immunity among PLHIV. The search methods and selection criteria include randomized controlled trial on nutritional interventions, specifically; effect of zinc on immune status of PLHIV was conducted. An extensive search from databases like ProQuest, PubMed, Cochrane and Science Direct was conducted from 28/04/2022 to 28/05/ 2022, a total of 05 studies were included after screening with PEDro scale and preferred reporting items for systematic reviews and meta-analyses (PRISMA) reporting to derive at a consensus on effect of zinc on immune status of PLHIV. Three reviewers independently screened and selected the trials for inclusion. The cumulative sample size from all the studies was 1329. As studies included were diverse meta-analysis was not possible. Four studies revealed that zinc supplementation was not effective in enhancing immune system of PLHIV whereas another 1 study showed that zinc supplementation is effective in boosting immune level among PLHIV. Zinc supplementation is beneficial and safe among PLHIV as it boosts immunity but further investigation is needed to generalize the findings.